THE MEAN STELLAR SPECTRA OF COOL GIANT STARS - Dragunova, A. V.; Belik, S. I.; Komarov, N. S. (Одеські астрономічні публікації, 2017)
The mean values of energy distributions in spectra of cool stars of various spectral types have been found using the Catalogue of spectra of 555 stars.